Nasjonalsosialistisk universitetspolitikk i Poznan og Oslo - Sem Fure, Jorunn (Folia Scandinavica Posnaniensia, 2007)
The article analyzes the different occupation policy of Germany in the university sector in Norway and Poland, focusing on the cases of Oslo and Poznan. The difference in occupational regime was decisive for the outcome. The different ranking of the Norwegian and Polish population in the nazi racial system led to an extremely brutal and destructive strike against Polish academics and institutions. The Polish university in Poznan was dissolved, the staff killed, deported or removed in other ways, and in 1941 the University reopened as a German, SS-dominated Reichs-University. Polish underground managed to continue some kind of academic activity and training, thus providing young people with learning and sources of self-esteem. In Oslo, the occupants attempted to draw the Norwegian academic elite into active collaboration, and bring about a slow turn of the liberal democratic institution into a national socialist defined university after the pattern of the earlier transformations taking place in Germany after 1933 and Austria 1938. The attempt failed, because the majority of staff and students put up resistance and refused to adhere. The policy changed after this failure, and in 1943 nearly 20% of the teachers were arrested along with 1200 students. Half of these students were deported to Germany for the rest of the war, in an attempt to re-educate them to embrace SS-ideology. This attempt failed as well - and not one of them volunteered to serve the German armed forces. Both the Polish and the Norwegian cases show the limitations of totalitarian use of power when confronted with the inner resistance based on liberal, democratic and patriotic values.